The growing complexity of customer engagement: a systematic review - Rosado-Pinto, F.; Loureiro, S. M. C. (EuroMed Journal of Business, 2020)
Purpose: The topic of customer engagement has been growing in relevance and complexity in the last decade. Therefore, the purpose of this paper is to systematically review and critically analyse the research about customer engagement and address the research question: “What marketing research has been conducted on customer engagement until now and what could be future avenues for research?” Design/methodology/approach: A systematic review of the existing literature is performed based on the Web of Science and Scopus electronic databases. A total of 144 articles are included in the final analysis. Findings: Customer engagement is perceived as a multidimensional concept with different definitions and sub-forms associated. There is an increasing number of authors studying the concept in different industries and geographies, with empirical studies being widely used. The concept emerges from specific theoretical pillars. Different constructs are associated with customer engagement, being studied as antecedents and/or outcomes. This study presents 8 major paths for future research. Research limitations/implications: This type of approach has a certain level of subjectivity, associated to the methodological process for choosing the articles to be included in the final analysis and the applied filters. Originality/value: Through this study, readers become aware of the state of the art on customer engagement and associated constructs, the gaps found in past research, the research contexts and also have a glimpse about what can be the future of this field of research, as well as research questions to be addressed.